Edukasi pencegahan hipertensi melalui media poster dengan metode think pair share terhadap pengetahuan dan sikap - Belkis, Happy Aprilia; Muhani, Nova; Yanti, Dhiny Easter (Published by: Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Ikatan Dokter Indonesia (IDI), 2025)
Background: Hypertension is now a health problem that is not only experienced by the elderly, but also by adolescents who are at risk of experiencing high blood pressure due to bad habits and unhealthy lifestyles. The prevalnce of hypertension in Lampung Province is 15.10 % of the 6.216.638 population aged 15 years and over. The high cases of hypertension in adolescensts today are caused by one of the low knowledge and attitudes about the risk factors for hypertension. It is necessary to in increase adolescent knowledge and attitudes thourgh poster media with the think pair share method, which is not yet known how effective this method is in increasing knowledge and attitudes in adolescent student. Purpose: To determine the differences in knowledge and attitudes towards preventing hypertension in adolescents through poster media with the think pair share method. Method: This study employed a quantitative research design with a quasi-experimental approach. The population consisted of 185 students from grades 10 and 11. The sampling technique used was proportional simple random sampling. Data were collected through a questionnaire. Data were analyzed using univariate (frequency distribution) and bivariate (Wilcoxon) tests. Results: There was a difference in knowledge (p-value = 0.001) and attitudes (p-value = 0.001) between posters and the think-pair method. Conclusion: Schools use posters and the think-pair-share method when providing hypertension education materials. Keywords: Attitude; Adolescents; Hypertension Prevention; Knowledge. Pendahuluan: Hipertensi kini menjadi masalah kesehatan yang tidak hanya dialami oleh lansia, tetapi juga oleh remaja yang berisiko mengalami tekanan darah tinggi akibat kebiasaan buruk dan gaya hidup tidak sehat. Prevaleni hipertensi di Provinsi Lampung sebesar 15.10% dari 6.216.638 penduduk berusia 15 tahun ke atas. Tingginya kasus hipertensi pada remaja saat ini disebabkan salah satunya pengetahuan dan sikap yang rendah tentang faktor risiko kejadian hipertensi. Perlu meningkatkan pengetahuan remaja dan sikap melalui media poster dengan metode think pair share yang belum diketahui bagaimana efektifitas metode ini dalam meningkatkan pengetahuan dan sikap pada siswa remaja. Tujuan: Untuk mengatahui perbedaan pengetahuan dan sikap terhadap pencegahan hipertensi pada remaja melalui media poster dengan metode think pair share. Metode: Penelitian ini menggunakan desain penelitian kuantitatif dengan pendekatan quasi ekperimen. Populasi dari penelitian dari kelas 10 dan 11, yakni sebanyak 185 siswa. Teknik pengambilan sampel proposional simple random sampling. Teknik pengumpulan data melalui lembar kuesioner. Analisis data menggunakan unvariat (distribusi frekuensi) dan bivariat (wilcoxon). Hasil: Ada perbedaan pengetahuan (p-value = 0.001) dan Sikap (p-value = 0.001). dengan media poster dan metode think pair. Simpulan: Sekolah menggunakan poster dengan metode think pair share pada saat memberikan materi penyuluhan hipertensi. Kata Kunci: Hipertensi; Pencegahan Remaja; Pengetahuan; Sikap.